Catalisadores de Cu/CeO2 modificados com La aplicados à reação de deslocamento gás-água - Silva, Tatiana de Freitas (2013)
The water gas shift reaction (WGSR) is often used in industrial processes in order to increase hydrogen production, as well as to remove quantities of CO in the chains produced by steam reforming of hydrocarbons. In this work, CuO/CeO2 and CuO/CeO2-La2O3 catalysts were prepared for application in the watergas shift reaction. The CeO2-La2O3 and CeO2 supports were prepared by three different methods: Hydrothermal (CeO2-La2O3(H) and CeO2 (H)), Co-precipitation (CeO2-La2O3(CP) and CeO2 (CP)) and Sol-gel ( CeO2(SG) and CeO2- La2O3(SG)). The La2O3-CeO2 supports were prepared according to the following molar ratios: 2:1, 1:1 and 1:2 (CeO2-La2O3). The activated catalysts were tested in the water gas shift reaction at temperatures between 150°C and 350°C and the formed products were analyzed by gas chromatography. The CO:H2O molar ratio used in all catalytic tests was 1:5. The catalysts Cu/CeO2(H), CuO/1CeO2-1La2O3(H), CuO/CeO2(CP), CuO/1CeO2-2La2O3(CP) and CuO/CeO2(SG) were also tested at 350°C for 24 hours in the shift reaction under the ideal situation (Reactor Feed: CO, N2 and H2O) to verify their stability. The catalysts CuO/CeO2 (H) and CuO/1CeO2-1La2O3(H) were also tested in the shift reaction under the real situation (Reactor Feed: CO, H2O, N2, H2 and CO2) for performance evaluation in a situation closer to the actual composition of the products observed at the output of industrial reformers. From the results it was observed that the addition of La to the CuO/CeO2 catalyst led to its structural stabilization by preventing the specific area decrease. The addition of La2O3 to the CuO/CeO2 catalysts caused a higher interaction of CuO with the supports, thereby preventing sintering of CuO, even during the reactions. XANES measurements in situ at the Cu edge confirmed the presence of Cu reduced during the course of the reaction, suggesting the presence of Cu sites with similar electron density. XANES spectra at the Ce edge confirmed that there were small changes in the oxidation state of Ce and that Ce species are more oxidized in the catalyst in which La is present. The presence of La probably contributed to higher stabilization of ceria and increased the mobility of oxygen due to vacancy formation in the CeO2 network. Catalysts whose supports were prepared by the hydrothermal method resulted in materials with higher specific area and higher catalytic activities and were more stable with respect to those obtained by the two other methods, during the 24 hours of reaction at 350°C. Therefore, the Cu/CeO2 (H) and Cu/1CeO2-1La2O3(H) catalysts show to be promising as catalysts for the shift reaction. We also observed that the support preparation process affected some properties of the material, such as phase formed, particle size, metallic area, dispersion, surface area and catalytic performance.